Categories and competition - CATTANI, Gino (Institutional Knowledge at Singapore Management University, 2017)
In this paper, we review, integrate, and extend the literature on markets, competition, and categories as it applies to strategic management theory. Developments in the literatures of economics and organizational theory have shed new light on market categories and category dynamics. These developments highlight the fact that boundary questions are fundamental to the competitive process, and represent a fertile area for research and theory. The objective is to encourage a theoretically grounded rapprochement between current strategic management research and both older and newer research on categories and competition.